The Scriptural Dilemma - Grimes, John Allen (1982)
The aim of all Scripture is to reveal the ultimate unity which lies hidden within the whole of existence. This means that there is a basic structure or ground upon which both objective and subjective being is based. Reality is a whole, through and through. Scripture reveals this unity by pointing towards that which is: the most comprehensive, the most immediate, the simplest, and of the greatest experiential content.
Keywords: Scriptural Dilemma